PERIKATAN DAN PERJANJIAN DALAM HUKUM ISLAM - Fauzi, Moh. (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
This study is a study of ushul fiqh relates with the law of the transaction between individuals in relation to the property. In that transaction is sometimes used the term of the engagement (al-iltizam) and agreement (al-?aqd), both of which are often interpreted and used in different contexts. Iltizam is closely related to the case of al-haq (right), which is something that arises as a form of human relations. Therefore, the fulfillment of such right is bound by rules that must be complied with. In addition, sometimes arising form the relationship between humans, sometimes in the form of the agreement. Both became important in the discussion of Islamic law.